Prevention and Mitigation of Extremism in Games: A Neomaterialist Reflection on the Agency of Objects - Carvalho, Evelise Galvão de (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2025)
Introduction: Digital games have become vulnerable to extremist propaganda yet offer prevention opportunities through their technological materiality. Games function as dynamic ecosystems formed by networks of human and non-human actors that directly impact player experiences. Objectives: This article investigates how technological elements in video games act as active agents in preventing and mitigating extremism, examining game materiality through a neomaterialist perspective that recognizes non-human agency in shaping player experiences. Methodology: This qualitative study combines systematic literature review, case analysis, and document examination. The research draws on neomaterialist theory (Latour, Barad, Bennett, Braidotti) and analyzes moderation mechanics in League of Legends, Valorant, Minecraft, Journey, and Overwatch. Results/Discussion: Analysis reveals object agency manifests through cooperative design mechanics, automated moderation systems, positive reinforcement tools, and AI-driven responses. However, reactive approaches often fail as companies implement post-problem solutions rather than preventive strategies from conception phases. Conclusions: The study proposes Safety by Design approaches integrating extremism prevention from early development stages, including inclusive design mechanics, AI-enhanced moderation, and distributed agency systems empowering players as prevention agents, demonstrating how object agency can create safer collaborative gaming environments.